Perceived Distress by Physicians in a Private Hospital in Mexico City - Adriana Panayi; Angel Flores; Maria Elizaga; Guido Cohen; Jimmy Cojab (Mashhad University of Medical Sciences, 2021)
Background: Medical education has undergone significant transformations to adapt to the modern work environment with its unique demands and challenges. Psychological manifestations secondary to stress are reported to have increased in physicians in training due to increasing performance and learning demands of both the work and social environment.  In this survey study, we sought to determine the extent of psychological distress amongst physicians in training, that is residents and interns, establishing patterns in terms of type of residency and stage of training. Methods: This is a cross-sectional, observational study conducted between March and July 2019 using a printed version of the perceived stress scale (PSS) survey, healthcare professionals (residents and interns) were surveyed  during their academic and patient care activities at a private hospital in Mexico City to asses their levels of distress. Results: A total of 101 physicians were invited to participate, of whom, 85 answered the survey (response rate 84%).  A high prevalence of moderate-high stress was noted in 55.3% of the study population (47/85). In addition, residents who were relatively new to their post were more likely to display higher levels of stress compared to their peers at advanced stagesConclusions: Residents and interns at our center experience moderate to high levels of distress. Stress management strategies should be targeted towards physicians early on in their training and awareness must be improved on this factor that may significantly impact academic performance and patient care.